Keefektifan Media Sosial sebagai Media Pembelajaran Pendidikan Agama Islam di SMKS 16 Farmasi Bengkulu - Nanik, Nanik (ISTISYFA: Journal of Islamic Guidance and Counseling, 2024)
Teaching Islamic Religious Education in the digital era has its own challenges for teachers as facilitators. This study aims to show the effectiveness of the role of social media as a learning medium in the digital era. This study uses a quantitative descriptive method using an online questionnaire with the research subjects of grade XII students of the Industrial Pharmacy Department and Community Clinical Pharmacy who were randomly selected as many as 62 students. Based on 4 aspects of the assessment, namely 1) effectiveness of social media use, 2) ease of use of social media, 3) student involvement, and 4) effectiveness of material delivery, an average score of 54.5 was obtained, indicating that social media is effective as a learning medium for Islamic Religious Education.Keywords: effectiveness; media; social; learning.